HEALTH FOR EARLY CHILDHOOD IN THE ERA 6.0 - Ummamah, Futiha Muhibbatul; Pramono, Pramono; Munaisra, Munaisra (Proceeding of International Conference on Multidisciplinary Research, 2024)
Nutrition is a food substance that is very important for the growth of early childhood. Nutrients are substances needed by the body such as producing energy, immunizing immunizations, building tissues in the body, and so on. It can be said that adequate nutrition can affect the physical and cognitive development of children. The physical development and cognitive abilities of children can be seen from what habits are consumed by the mother. Everything consumed by the mother affects the development of the fetus, especially during the last trimester. During the last trimester of pregnancy, you need foods that contain nutrients in the form of milk, vitamins and potassium. These nutrients are important not only to make it easier for pregnant women in the delivery process but also for the development of the future baby in the womb. The body of both adults and young children needs foods that contain balanced nutrition. Besides being needed by the body, food that contains balanced nutrition is also needed by the brain so that during the stimulation process the child quickly responds to the stimulus given and maintains immunity so that he is not susceptible to disease because, at this age, children are very susceptible to disease. Therefore parents and teachers of early childhood need to broaden their insights regarding the urgency of intake of foods that contain balanced nutrition for early childhood and their benefits. Increasing nutritional intake in children requires a variety of different foods every day so that children are interested in consuming them but the nutritional content in these foods is not reduced. So that the nutritional content in these foods does not decrease during the food processing process, knowledge of balanced nutrition is needed as explained by the Ministry of Health in the General Guidelines for Balanced Nutrition as a guide for the public to know what is good and needed for their baby's intake